Analytical Heat and Fluid Flow in Microchannels and Microsystems - Cotta, Renato M.; Knupp, Diego C.; Naveira-Cotta, Carolina P. (Mechanical Engineering Series,, 2016)
This book focuses on the modeling and analysis of heat and fluid flow in microchannels and micro-systems, compiling a number of analytical and hybrid numerical-analytical solutions for models that account for the relevant micro-scale effects, with the corresponding experimental analysis validation when applicable. The volume stands as the only available compilation of easy to use analytically-based solutions for micro-scale heat and fluid flow problems, that systematically incorporates the most relevant micro-scale effects into the mathematical models, followed by their physical interpretation on the micro-system behavior.